The eighteenth-century music manuscripts at St Patrick's Cathedral, Dublin: sources, lineage, and relationship to other collections - Houston, Kerry (Trinity College Dublin. School of Drama, Film and Music., 2002)
This thesis examines the music manuscripts copied before 1800 that survive in the music library at St Patrick?s Cathedral, Dublin. Prior to this study, these manuscripts had not been investigated in a comprehensive way. The aim of this investigation is to record textual detail of the manuscripts and to examine their provenance and lineage in the wider context of the cathedral?s history and the history of cathedral music in the British Isles.
Keywords: Music; St Patrick's Cathedral; manuscripts; Dublin